Profitability Transmissions Among Polish Economic Sectors - Marek WIERZBIŃSKI; Zofia WIERZBIŃSKA (Communications of International Proceedings, 2024)
Dynamics is one of the key attributes defining the modern economy, the most constant element being change. The economic situation changes over the years - affecting the asset and financial situation of the constituent entities, but also as a consequence of changes taking place within those entities. Also to be included in the network of dependencies is the interaction of economic actors, the effects of which are visible with more or less delay. Entities in the market economy are interested in maximising their value, and one of the intermediate objectives in pursuit of the main objective is to maximise profitability, i.e. the entity's ability to generate profits. This ability, in the long term, is a determinant of the entities' functioning and development. Consequently, business entities commonly analyse the level of their profitability, most often comparing it to industry results - to position the effects of their activities against those of their competitors. It is much less common to analyse the level of profitability in relation to entities in other sectors, without considering them as a direct benchmark in the assessment. What is underestimated, however, are the interrelationships and dependencies that exist between sectors and which may, over a certain period of time, have a significant impact on the situation of other sectors. Cross-sectoral transmission studies can be encountered in the literature; however, they mainly focus on the market value of entities' shares or in an international perspective (Ehrmann, Fratzscher, Rigobon 2011, Gjika, Horvath 2013, Bein, Tuna 2015, Yarovaya, Brzeszczynski, Lau 2016, Grabowski 2018, 2019, Moagăr-Poladian, Clichici, Stanciu 2019, Jawadi, Chlibi, Cheffou 2019, Nguen 2022, Urjasz 2023). The authors of this study reach inside economic entities and analyse their profitability indicators - at different levels, within different sectors, over a period of 20 years. This is because the aim of this article is to examine the links between the level of profitability of entities operating in different sectors of the Polish economy and to demonstrate the intersectoral transmission of profitability. The authors' hypothesis is that a decrease or increase in profitability in particular sectors, entails a decrease or increase in profitability in related sectors. The essence of the study is to measure the direction and strength of this transmission, as well as to determine between which sectors the transmission is greatest.......